The Effect Of GDP And Foreign Investment On The Value Of Exports And Imports According To The International Trade Classification (Sitc) Standard Group In Indonesia In The Islamic Economic Perspective In 2013-2022 - Oktafia, Selva; Citra Etika; Muhammad Yusuf Bahtiar (Cattleya Darmaya Fortuna, 2025)
International Trade (Export-Import) is one of the most important indicators in an economy. With the existence of international trade, every country in the world can exchange resources owned by each country, with the aim that there is no excess or shortage of resources in each country in the world. This study aims to analyze GDP and foreign investment on Export-Import (SITC). This study uses a quantitative approach with Error Correction Model (ECM) analysis method with Eviews 12. The Data used in this study are annual export-import data (SITC), GDP and foreign investment from 2013-2022. The type of research used in this study is Library Research. The results of this study showed that Gross Domestic Product in the short term does not affect the Export-Import (SITC), while in the short term negatif a significant negative effect on Export-Import (SITC). Foreign investment in the short and long term berpengaruh negatif has a significant negative effect on Export-Import (SITC) in Indonesia. In the Islamic economic perspective, international trade may be carried out on the condition that the product does not contain haram elements in it according to the Qur'an and Hadith.